Preservice mathematics teacher knowledge of higher order thinking skills - Nenohai, Juliana Mehelina Herlince; Dao Samo, Damianus; Garak, Siprianus Suban; Rimo, Imelda Hendriani Eku; Soko, Imelda Paulina (Intelektual Pustaka Media Utama, 2024)
This study aims to describe preservice mathematics teacher knowledge of higher order thinking skills in terms of definition, Bloom's taxonomy level, curriculum, learning, and evaluation. This research is quantitative research with a survey method. and sample consisted of 248 preservice mathematics teachers in semesters VI - VIII of the Department of Mathematics Education, Nusa Cendana University, Timor University, and Wira Wacana Sumba University. The instrument used was a questionnaire about high order thinking skill (HOTS) which consisted of 105 statements. Data analysis used Likert's summeted rating, one sample test, Mann Whitney, Kruskall-Wallis tests, multiple linear regression test, and multivariate analyisis of variance (MANOVA) test. The results showed that the knowledge level of preservice mathematics teacher was in the good category. Based on gender differences, there was no significant difference in the average knowledge of preservice mathematics teacherabout HOTS, there was a significant difference in the average knowledge of preservice mathematics teacher about HOTS which is significant based on differences in academic ability and gender differences do not significantly affect knowledge about HOTS levels in Bloom's taxonomy, curriculum, and pedagogy while academic knowledge has a significant effect on HOTS knowledge of preservice teachers in almost all aspects except for pedagogy.